Post-translational modifications regulate microtubule function - Westermann, Stefan; Weber, Klaus (Nature reviews. Molecular cell biology, 2003)
Key Points The carboxy-terminal tails of α- and β-tubulin are essential for microtubule function. They lie on the outer surface of the microtubule where they can influence the binding of associated proteins. With the exception of acetylation, the post-translational modifications of microtubules — that is, detyrosination/tyrosination, formation of Δ2-tubulin, polyglutamylation and polyglycylation — are all located in the carboxy-terminal tails. Acetylation of α-tubulin can be abolished without consequences in Tetrahymena , but it seems to have a function in cell motility. Two histone deacetylases, HDAC6 and SIRT2, have been shown to function as tubulin deacetylases. Genetic analysis of polyglycylation in Tetrahymena demonstrates its essential function in the organization of axonemes, cell motility and cytokinesis. Polyglutamylation can influence the binding of structural and motor microtubule-associated proteins (MAPs) to microtubules. Antibody-injection studies indicate an important role for polyglutamylation in centriole stability. The functional role of the tyrosination cycle of tubulin is still unclear; cells cultured with low activity of the tubulin tyrosine ligase (TTL) enzyme show no obvious defects. TTL-knockout mice, however, die early in development owing to an as-yet-uncharacterized defect. The αβ-tubulin heterodimer, the building block of microtubules, is subject to a large number of post-translational modifications, comparable in diversity to the intensively studied histone modifications. Although these unusual modifications are conserved throughout evolution, their functions have remained almost completely elusive. Recently, however, important advances in the understanding of how tubulin modifications regulate function and organization have been made.